Struktur Anatomi dan Kualitas Serat Kayu Parashorea malaanonan (Blanco) Merr. (Anatomical Structure and Fiber Quality of Parashorea malaanonan (Blanco) Merr.) - Supartini Supartini; Listya M Dewi (Masyarakat Peneliti Kayu Indonesia, 2010)
Parashorea malaanonan (Blanco) Merr. is one of Dipterocarps species that listed in Red List IUCN as critically endangered species. The evaluation of its suitability for pulp and paper raw material was also needed. The samples were observed by using Johansen’s Method for the microtome slide making and for the observation of anatomical structure were using IAWA List. The maceration process was using FPL’s method and fibre quality criteria according to Rahman and Siagian (1976). The results shows that P. malaanonan have light brown heartwood and yellow pale sapwood; rough texture; grain straight to interlocked, and impression touch rough. The main microscopic characters are growth ring indistinct, vessels diffuse arranged diagonally, vessels mostly solitary with outline rounded. Tyloses were found in vessels, perforation plate simple, intervessel pits scalariform to opposite. Axial parenchyma paratracheal thin vasicentric, rays uniseriate and multiseriate. Axial intercellular canals in long tangential lines and axial canals diffuse. Vasicentric tracheids present, thin wall fibre (4 μm), fibre length 1368 μm, and diameter 25 μm. Prismatic chrystals in ray cells and chambered axial parenchyma cells. The fibre quality of P. malaanonan belongs to the quality class II, which mean moderately good for pulp and paper.